[Jornada a Campo] - Blanco, Lisandro Javier; Ferrando, Carlos Alberto; Avila, Roxana Edith; Ricarte, Ramon Armando; Namur, Pedro Ramón; Agüero, Walter Damian; Luna Toledo, Emanuel Santiago; Sancho, Alicia Roxana (Estación Experimental Agropecuaria La Rioja, INTA, 2024)
Ciclo de Jornadas técnicas 2017 del Centro Regional Catamarca-La Rioja